1992
DOI: 10.1891/0886-6708.7.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dating Violence: A Multivariate Analysis

Abstract: A multivariate approach was used to determine the pattern of predictors associated with engaging in dating violence. Predictors were selected whose relationship to dating violence has been established by earlier research: attitudes toward violence, sex-role attitudes, romantic jealousy, general levels of interpersonal aggression, verbal aggression, and verbal and physical aggression received from one’s partner. Participants included 305 introductory psychology student volunteers (227 females and 78 males) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
149
2
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 38 publications
22
149
2
12
Order By: Relevance
“…Participants who expressed to have committed violence in a relationship had higher acceptance levels of dating violence compared to those who didn't commit violence. This finding is supported by Bookwala, Frieze, Smith, and Ryan (1992), who found that attitude towards violence predicted violent behaviors. Another explanation is that the individuals justified violence in order to avoid criticizing their own behaviors.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Participants who expressed to have committed violence in a relationship had higher acceptance levels of dating violence compared to those who didn't commit violence. This finding is supported by Bookwala, Frieze, Smith, and Ryan (1992), who found that attitude towards violence predicted violent behaviors. Another explanation is that the individuals justified violence in order to avoid criticizing their own behaviors.…”
Section: Discussionsupporting
confidence: 54%
“…The literature indicates that men have higher attitudes towards male psychological dating violence (Price et al, 1999). Moreover, both national and international literature shows that men have higher acceptance levels of dating violence compared to women (Mercer, 1988;O'Keefe, 1997;Sezer, 2008;Bookwala, Frieze, Smith, & Ryan, 1992). Considering the Turkey's cultural characteristics, it can be stated that the paternalistic structure is dominant, and the men can be expressed to play an approving role of the existent dating violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that more females than males reported physical dating violence perpetration did not surprise us, however, as more than 15 prior studies have also found female adolescents to report more dating violence perpetration than males. 24,34,36,[57][58][59][60][61][62][63][64][65][66][67][68][69] As stated in the Introduction, it is our view that the prevention of "common" dating violence is important and merits research attention because of the potential for even non-severe physical violence to result in harm, and because it has the potential to normalize the use of physical assault in all types of interpersonal relationships.…”
Section: Limitationsmentioning
confidence: 99%
“…An individual's attitude toward both male perpetrated and female perpetrated dating violence influences the likelihood of that individual becoming involved in a violent dating relationship in the present (Medeiros & Straus, 2004;O'Keefe, 1997;Bookwala, Frieze, Smith, & Ryan, 1992). Partners who hold attitudes that endorse dating violence are more likely to have been abusive in their relationships (Bookwala et al, 1992;O'Keefe, 1997) and to perpetrate dating violence later in life, particularly for males (Foshee et al, 2001). Data on females' attitudes toward dating violence in relation to actual perpetration is more limited compared to studies on males.…”
Section: Attitudes Toward Dating Violencementioning
confidence: 99%